Is less more? Intravenous immunoglobulin for pediatric immune thrombocytopenia - Eyal Elron; Joanne Yacobovich; Orly Efros; Osama Tanous; Sarina Levy-Mendelovich; Esti Shamba; Orna Steinberg-Shemer; Tracie Goldberg; Shai Izraeli; Oded Gilad (Therapeutic Advances in Hematology)
Objectives: Treatment of pediatric immune thrombocytopenia (ITP) is guided by the risk of bleeding. Intravenous immunoglobulin (IVIg) is one of the first-line therapy options for new-onset pediatric ITP. However, the exact optimal dose of IVIg has not been determined. Methods: This retrospective cohort study included all hospitalized children with newly diagnosed ITP receiving IVIg as first-line therapy during 2010–2020. We compared the safety and efficacy of two common IVIg dose regimens, 1 and 2 g/kg. Outcomes were short and long-term treatment responses and adverse events to the different doses. Results: A total of 168 children were included in our cohort. Eighty-two children were treated with 1 g/kg of IVIg and 86 with 2 g/kg. There was no difference in sustained response (platelet count > 20 × 10 9 , > 14 days) between the groups (74.3% vs 76.7%, respectively, p  = 0.72) and maximal platelet counts following treatment ( p  = 0.44). No difference was found regarding the percentage of chronic ITP between the two groups (24.4% in the 1 g/kg group as compared to 17.4% in the 2 g/kg group; p  = 0.34). Logistic regression analysis demonstrated there was no effect of the IVIg dose on treatment failure and development of chronic ITP. As anticipated, 47.7% of adverse events were in the 2 g/kg group and 32.9% in the 1 g/kg group, with borderline statistical significance ( p  = 0.06). Conclusion: The initial treatment of newly diagnosed pediatric ITP using a 1 g/kg IVIg regimen may give comparable results to the double dose of 2 g/kg in attaining a prolonged safe hemostatic threshold, without impacting the incidence of chronic disease.